Profil Kompetensi Guru SD Pasca Sertifikasi - Umar, Syahwani (Universitas Tanjungpura, 2016)
Teacher quality improvement program has been implemented by the government starting with the establishment of minimum standards of the teachers’competence including: pedagogical competence, personal competence, professional competence, and social competence.In general, the elementary school level teacher’s competence, post-certification, is still at a low level. The ability of teachers at the four competency primarily on professional competence and pedagogical competence has not described the behavior as a professional teacher. In fact, the teachers have been certified.The research results were as follow: 1) Professional competence indicated that teachers relativelymaster the teaching materials, students, skill in selecting and using teaching methods, and be exemplary in appearance and speech in the classroom and at school and in the community; 2) pedagogical competence demonstrated that teachers relativelymake learning design and manage learning, develop curricula, conduct evaluations and guide students to actualize their potential; 3) The personal competence demonstrated that the teachers’ personal capacity relatively reflects the personality of a solid, stable, mature, wise and authoritative, a role model for students, and noble; and 4) social competence shown that teachers are relatively able to communicate and interact effectively with students, with peers, parents/guardians of students and the surrounding community.